TATA KELOLA SAMPAH DI KOTA PEKANBARU (STUDI KASUS PADA BANK SAMPAH DI KOTA PEKANBARU TAHUN 2016) - Jery Nov Pratama; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In order to overcome the garbage problem in Pekanbaru City, referring to Government Regulation No. 81/2012 on Household Waste Management and Garbage of Household Garbage, Minister of Environment Regulation No. 13/2012 on Guidelines for Reduce, Reuse and Recycle Implementation through Waste Bank, and Pekanbaru City Regulation No. 8 Year 2014 on Waste Management, Pekanbaru Municipal Government together with the community work together in implementing waste management in Pekanbaru City through the application of 3R method and the establishment of Bank Trash. However, the application of 3R method and the establishment of Waste Bank is still not effective in overcoming the garbage problem in Pekanbaru City. This is due to the lack of awareness and knowledge of the community to participate in waste management in Pekanbaru City through the Garbage Bank program. In this research, there are two problem formulation: "How is the waste management in Pekanbaru city through the garbage bank program of 2016 and what are the factors that hamper the waste management in Pekanbaru city through the garbage bank program of 2016". The research method used in this research is qualitative descriptive research method, where in this research the researcher tried to explain about the waste management in Pekanbaru City through the Garbage Bank program in 2016. Then the data collection techniques in this study using interview, observation and documentation data and facts related to research problems. Further data obtained from the research location will be processed and analyzed further by way of describing the facts that have been found from the location of the study.From the results of interviews to informants and based on the data and information obtained by researchers when doing research, it can be concluded that Garbage Management in Pekanbaru City Through Waste Bank Program Year 2016 which can be classified into 4 (four) aspects of the discussion, the Regulation Legislation Related to Waste Management and Formation of Garbage Banks, Establishment of Garbage Banks, Waste Bank Formation Mechanisms, and Waste Bank Operations. Furthermore, the impediments to the implementation of the Garbage Bank in Pekanbaru City in 2016 are the lack of socialization related to the Waste Bank program, the lack of budget in supporting the Bank Trash program, the lack of technical training related to Garbage Bank, Inadequate Bank Garbage Facilities and Infrastructure, Bank Waste program.Keywords: Waste Management, Waste Bank Program, Pekanbaru City